Sorghum and Sesame Markets Performance under Climate Change in Sudan - B., Elgali M.; H., Mustafa R.; D., Kirschke (Gezira Journal of Economic and Social Sciences; مجلد 8 عدد 2 (2017), 2017)
Sorghum and sesame are produced under the rain fed sector in Sudan; they are competing each other for agricultural input and resources since they are grown in the same season. The purpose of this paper is to examine sorghum and sesame performance under climate change, including supply, demand, exports and imports and food security variables. The economic performance of the country particularly agriculture; depends on weather conditions especially rainfall. Summer rainfall pattern has been decreasing by 15 to 20 percent in the last forty years. The study has developed a stochastic multi-market model for sorghum and sesame, the model comprices important characteristics of agriculture in Sudan including the dependency of agricultural supply on rainfall. Sorghum and sesame markets have been simulated by calibrating supply and demand functions; the climate scenario simulates sorghum and sesame under climate change of rainfall with a decreasing trend of 20%. The model has introduced prices and rainfall as stochastic variables; it has also incorporated food security indicators, which are directly affected by the agriculture performance. The uncertain stochastic variables in the model are presented in their Cumulative Distribution Functions (CDFs) by the help of BestFit; a software within the @Risk program based on annual observations from 2000-2013. The final results are graphed in the form of Cumulative Distribution Function (CDF). The model scenario simulations revealed that, the impact of the decreasing trend of rainfall would overall lead to considerable losses in sorghum and sesame supplies and hence a deterioration in the country’s external sector and food security situation.